2011
DOI: 10.1016/s1734-1140(11)70619-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of LASSBio-998, a new drug candidate designed to be a p38 MAPK inhibitor, in an experimental model of acute lung inflammation

Abstract: We investigated the effects of LASSBio-998 (L-998), a compound designed to be a p38 MAPK (mitogen-activated protein kinase) inhibitor, on lipopolysaccharide (LPS)-induced acute lung inflammation in vivo. BALB/c mice were challenged with aerosolized LPS inhalation (0.5 mg/ml) 4 h after oral administration of L-998. Three hours after LPS inhalation, bronchoalveolar lavage fluid was obtained to measure the levels of the proinflammatory cytokines TNF-α (tumor necrosis factor-α) and IL-1 (interleukin-1) and the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Many RBPs are substrates of the p38 MAPK pathway, implying these proteins are part of signaling pathways responding to proinflammatory stimuli [112,113]. A strong link has been established between the p38 pathway and inflammation, including known roles in rheumatoid arthritis, Alzheimer’s disease, inflammatory bowel disease, as well as endotoxin-induced shock, collagen-induced arthritis, and acute lung inflammation [114118]. In addition, inflammatory cytokines such as TNFα and IL-1 as well as LPS and environmental stresses are known catalysts of initiating p38 signaling.…”
Section: P38 Regulation Of Rbps: a Counterregulatory Mechanism?mentioning
confidence: 99%
“…Many RBPs are substrates of the p38 MAPK pathway, implying these proteins are part of signaling pathways responding to proinflammatory stimuli [112,113]. A strong link has been established between the p38 pathway and inflammation, including known roles in rheumatoid arthritis, Alzheimer’s disease, inflammatory bowel disease, as well as endotoxin-induced shock, collagen-induced arthritis, and acute lung inflammation [114118]. In addition, inflammatory cytokines such as TNFα and IL-1 as well as LPS and environmental stresses are known catalysts of initiating p38 signaling.…”
Section: P38 Regulation Of Rbps: a Counterregulatory Mechanism?mentioning
confidence: 99%
“…Inhibition of p38 MAPK using SD‐282 reduces inflammation in a model of tobacco smoke‐induced airway inflammation with decreased expression of cyclooxygenase‐2 (COX‐2) and IL‐6 mRNAs . Studies using pharmacological inhibitors have also implicated p38 MAPK in mouse models of COPD, asthma and acute lung inflammation , suggesting that p38 MAPK inhibition could have therapeutic effects in lung inflammatory diseases.…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…Inhalation of LPS has previously been used to induce neutrophilic airway inflammation in humans [ 27 ], laboratory animals [ 28 ], and horses [ 22 , 29 ]. Several studies have shown that inhalation of LPS led to increased neutrophil counts and increased neutrophil ratios in BALF six hours after the challenge in healthy horses [ 22 , 29 ].…”
Section: Discussionmentioning
confidence: 99%